1979
DOI: 10.1104/pp.63.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Fixation by Lupin Root Nodules

Abstract: Labeling studies using detached lupin (Lupinus angustifofius) nodules showed that over times of less than 3 minutes, label from 13,4-'4Clglucose was incorporated into amino acids, predominantly aspartic acid, to a much greater extent than into organic acids. Only a slight preferential incorporation was observed with 11-14C1-and 16-"4Cjglucose, while with IU-_4C1-glucose more label was incorporated into organic acids than into amino acids at all labeling times. These results are consistent with a scheme whereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…To distinguish between the possible association of dark CO2 fixation by PEP carboxylase with nitrogenase activity and with NH3 production (and assimilation), an attempt was made to inhibit these processes differentially (Table III) From the results of the two treatments, it was concluded that a major portion ofdark CO2 fixation was associated more closely with nitrogenase activity than with NH3 production and assimilation. Similar results were obtained by Laing et al (11) with He:02 and 100% 02, and Coker and Schubert (5) with acetylene. From the results of the present study, it is suggested that the excess CO2 fixation provides organic acids for oxidation (presumably in bacteroids) to provide ATP and reductant in support of nitrogenase activity.…”
Section: Methodssupporting
confidence: 81%
“…To distinguish between the possible association of dark CO2 fixation by PEP carboxylase with nitrogenase activity and with NH3 production (and assimilation), an attempt was made to inhibit these processes differentially (Table III) From the results of the two treatments, it was concluded that a major portion ofdark CO2 fixation was associated more closely with nitrogenase activity than with NH3 production and assimilation. Similar results were obtained by Laing et al (11) with He:02 and 100% 02, and Coker and Schubert (5) with acetylene. From the results of the present study, it is suggested that the excess CO2 fixation provides organic acids for oxidation (presumably in bacteroids) to provide ATP and reductant in support of nitrogenase activity.…”
Section: Methodssupporting
confidence: 81%
“…The cost in terms of ATP could vary depending on the P/2e ratio of the oxidative phosphorylation being different from 3. Support for CO2 fixation varying with total nitrogenase activity can be gained from the loose correlation between these processes in other legumes and cultivars of soybean (3,4). However, under an environment ofAr.02, similar to the measurement conditions in this study, the relationship between CO2 fixation and nitrogenase function could not be shown in lupin (10), and these authors suggested that nodule CO2 fixation may be primarily a function of ammonia assimilation (10). If CO2 fixation in fact varied with total e flow, then the cost estimated by the slope would be a minimal value and can be regarded throughout the discussion as a minimum of 2 C02/e pair since root respiration declined only slightly as nodule respiration decreased.…”
Section: Resultsmentioning
confidence: 40%
“…13 fixation via nodule PEP3 carboxylase (EC 4.1.1.3 1) acts as a mechanism for recovery ofsome ofthis respired C02, thus increasing nodule efficiency and providing an added source of carbon for assimilation of fixed N. Studies with lupine and soybean suggest different relationships between N2 fixation and PEP carboxylase. In lupine, manipulations that reduced nitrogen fixation activity caused a concomitant decrease in PEP carboxylase activity (12). Coker and Schubert (7) found that CO2 fixation activity declined in advance of the decrease in N2 fixation activity in soybean nodules.…”
mentioning
confidence: 99%